Soft Photon Theorems in Bremsstrahlung and Photoproduction of Pions - Holland, Peter John (My University, 1970)
In the soft photon limit the bremsstrahlung cross-section is related to the corresponding elastic scattering cross-section in a model-independent manner. The cross-section for threshold photoproduction of pions becomes independent of the detailed pion-nucleon interaction if the ratio of pion to nucleon mass is made sufficiently small. These two results are a consequence of the gauge invariance of the scattering amplitude for a process involving one photon. We review the derivation of Low's bremsstrahlung theorem for spin-zero and spin-half particles, and outline an extension to all orders of photon energy. The theorem for photopion production is derived by the same method. A non-relativistic analogue to the Bremsstrahlung theorem is also considered.
Keywords: photon, bremsstrahlung, cross-section, photoproduction, pion, theorem